Occurrence of tephritid fruit flies with intermediate morphologies of Bactrocera carambolae and B. papayae (Diptera: Tephritidae) in Selangor, Peninsular Malaysia - Juma, Salim; Muhamad Awang, Rita; Adam, Nur Azura; Hee, Alvin Kah Wei; Gnanasegaram, Manjeri (American-Eurasian Network for Scientific Information, 2014)
Background: Tephritid fruit flies, Bactrocera carambolae(Drew and Hancock) and Bactrocera papayae (Drew and Hancock) belonging to the B. Dorsalis complex are key pests of valuable fruits in Southeast Asia. Control of these pests is often limited by difficulties on their identification that have been increasing due to recent occurrences of species with morphological characteristics of B. carambolaeand B. papayae (hereafter known as intermediates). Whilst field observations of mating between B. Carambolae and B. Papayae have not been documented, it was believed that this phenomenon had occurred through trapping of adult fruit flies with intermediate morphologies of the two mentioned species. This was also substantiated from results of laboratory crossing between B. Carambolae and B. papayae. Objective: A study was conducted to investigate the occurrence of intermediates and its proportion from their parental stocks based on field collection of flies infested starfruits, Averrhoa carambola L. and methyl eugenol-baited traps. Results: A total of 7,144 Bactrocera fruit flies were collected from infested fruits and another 12,522 male flies from traps were collected. A high proportion of intermediates (63%) were trapped whilst 25% of the flies from infested fruits accounted for intermediates. Conclusion: This study suggested that B. carambolae,B. Papayae along with their intermediates are pests of economic importance to starfruit in Malaysia. The study also has reported the predominance of B. Carambolae from damaged fruits and intermediates from methyl eugenol trapping capture; indicating that B. Carambolae is a major fruit fly species infesting starfruit however, intermediates are found in high proportion in fruit field environment.